Analisis Faktor-faktor Yang Mempengaruhi Tingkat Pertumbuhan Ekonomi di Provinsi Banten - Setiyawardani, Dinda Rindiantika; Nursabrina, Allya; Ramdhani, Rafli Saputra; Desmawan, Deris (Jurnal Informatika, 2024)
The aim of this research is to evaluate the variables that have an influence on the level of economic growth in Banten province in 2022. Employment level, human development index, unemployment rate, poverty level and level of income inequality are some of the variables studied. Using descriptive methodology, secondary data using the SPSS multiple linear regression application method from BPS Banten province is used to describe economic phenomena realistically. It is hoped that the results of the study will broaden insight into various factors that influence economic growth in Banten province. Findings-according to this research, only the labor force participation rate has a meaningful influence on economic development, while the human resource development index, the level of welfare deprivation, the level of lack of employment opportunities, and the level of income inequality are statistically insignificant. Engagement-This research can provide valuable knowledge about the elements that influence economic growth, which can be used to make decisions in the future.